Acquisition practice prior to commercial use in the European Union - Berde, Ágnes Barbara (Acta Agraria Debreceniensis, 2012)
The target of 3% of GDP spent on R&D by the Lisbon priorities seems to be still far away from the reality in some European countries and at EU level as well. The economic crisis determined the priorities and it makes more complicated to dedicate more budget on Research and Development. New methods, new measures are needed in the European Union. Measures that supporting the demand side of the innovation and generates market-pull affects. The Europe 2020 Innovation Union Flagship Initiative dedicates a special role to precommercial procurement for the upcoming 10 years. Nowadays, there are more and more European countries running pilot projects adapting the American SBIR (Small Business Innovation Research) programme.